PHENOMEN OF UNDEREMPLOYMENT IN THE LABOUR MARKET IN POLAND (Research Bulletins of the Faculty of Economic Sciences, 2022)
The aim of the article was to analyze the phenomenon of underemploymentin terms of gender equality in the labor market in Poland between 2005-2019.The article investigates whether the same tendencies of changes occure amongstunderempolyed men and women. In addition, the part-time employment was outlinedtogether with the employed and unemployed in Poland within the above-mentionedyears in order to examine the research problem more extensively. The author of thearticle used simple statistical tools, such as: analysis of the dynamics of changes in theform of a measure of relative increase with a variable base and the average rates ofchanges of the phenomenon over time. The conducted research allowed to determinethe average values in individual years and indicate the periods with the highest and thelowest results. Moreover, the applied tools made it possible to determine the annualchanges among the underemployed, employed and unemployed. The article uses datagained from the International Labor Organization together with literature related to thetopic of the examination including foreign literature.
Keywords: underemployment, unemployment, labour market, social problems, Poland